Watershed Modeling with ArcSWAT and SUFI2 In Cisadane Catchment Area: Calibration and Validation of River Flow Prediction - Iwan Ridwansyah; Hidayat Pawitan; Naik Sinukaban; Yayat Hidayat (International Journal of Science and Engineering, 2014)
Increasing of natural resources utilization as a result of population growth and economic development has caused severe damage on the watershed. The impacts of natural disasters such as floods, landslides and droughts become more frequent. Cisadane Catchment Area is one of 108 priority watershed in Indonesia. SWAT is currently applied world wide and considered as a versatile model that can be used to integrate multiple environmental processes, which support more effective watershed management and the development of better informed policy decision. The objective of this study is to examine the applicability of SWAT model for modeling mountainous catchments, focusing on Cisadane catchment Area in west Java Province, Indonesia. The SWAT model simulation was done for the periods of 2005 – 2010 while it used landuse information in 2009. Methods of Sequential Uncertainty Fitting ver. 2 (SUFI2) and combine with manual calibration were used in this study to calibrate a rainfall-runoff. The Calibration is done on 2007 and the validation on 2009, the R2 and Nash Sutchliffe Efficiency (NSE) of the calibration were 0.71 and 0.72 respectively and the validation are 0.708 and 0.7 respectively. The monthly average of surface runoff and total water yield from the simulation were 27.7 mm and 2718.4 mm respectively. This study showed SWAT model can be a potential monitoring tool especially for watersheds in Cisadane Catchment Area or in the tropical regions. The model can be used for another purpose, especially in watershed management.